Identification of human papillomavirus, Epstein-Barr virus and cytomegalovirus in paraffin tissues by molecular methods in patients with anogenital warts - Eroglu, Kubranur Sorkulu; Demir, Betul; Cicek, Demet; Toraman, Zulal Asci; Balta, Hilal; Celik, Mehmet Semih; Otlu, Baris (Taylor & Francis Ltd, 2025)
BackgroundAnogenital warts (AGWs) are typically caused by low-risk HPV types. Coinfection with EBV and CMV may influence disease progression, especially under immunosuppression. This study aimed to detect HPV, EBV, and CMV in tissue samples from AGW patients. This descriptive, retrospective, single-center study aimed to detect HPV, EBV, and CMV DNA in paraffin-embedded tissue samples from patients with AGWs.Material and methodsParaffin-embedded tissues from 24 AGW patients were analyzed using real-time PCR and pyrosequencing for HPV, EBV, and CMV DNA. Demographic and viral data were statistically evaluated. Degraded or insufficient DNA samples were excluded following quality control assessment. Descriptive and comparative statistical analyses were performed using SPSS v22.0.ResultsHPV was detected in 62.5% of patients, most commonly type 6, followed by types 40, 87, and 16. EBV was found in 2 patients (8.3%), both with HPV coinfection. HPV. CMV was not detected in any samples. No statistically significant associations were found between demographic or clinical parameters and viral positivity.ConclusionThe study identified rare EBV and HPV coinfections in AGWs but no CMV positivity. These findings are descriptive, and the small sample size limits generalization. The presence of EBV in immunosuppressed individuals may suggest immunotoxic mechanisms affecting viral persistence in the skin. Further studies with larger cohorts are warranted.
Keywords: Anogenital warts; HPV; EBV; CMV; immunosupression; immunotoxicity